Molecular dynamics study of hydrogen isotopes at the Be/BeO interface. (5th October 2022) - Hodille, E A; Byggmästar, J; Ferro, Y; Nordlund, K
Abstract: Molecular dynamics simulations are used to investigate the behaviour of D atoms at two interfaces between beryllium (Be) and beryllium oxide (BeO). After relaxation of the simulation cell, there are (a) localised defects at the interface and (b) a hexagonal misfit dislocation network creating a succession of compressed and expanded area from each side of the interface. The simulations between 750 K and 1500 K for tens to hundreds of nanoseconds show that both interfaces act as trapping sites for D atoms. The simulations also show that D atoms tend to migrate in the material where the hydrogen isotope solubility is the highest as predicted by thermodynamics. However, the simulations also shows that there are additional kinetic barriers (D trapping sites, D2 formation/dissociation in BeO) that slow down the path to equilibrium. These additional kinetic barriers may influence the fuel retention and permeation in Be materials.